Muscle Mass Adjusted for Body Weight Is Associated with Significant Liver Fibrosis in Young Adults with Nonalcoholic Fatty Liver Disease: A Cross-Sectional Study from a Korean Military Hospital - Jaejun Lee; Seongjoo Na; Taeyun Kim; Seong-Woo Lee; Myoung Jung Kim; Chang In Han; Si Hyun Bae (Journal of Obesity & Metabolic Syndrome, 2023)
Background : Sarcopenia has been associated with nonalcoholic fatty liver disease (NAFLD). This study aimed to investigate the correlation between liver fibrosis and muscle mass in young adults with NAFLD. Methods : We conducted a retrospective review of 88 Korean soldiers <35 years of age who underwent bioelectrical impedance analysis and liver stiffness measurements. A FibroScan-aspartate aminotransferase score >0.35 was used to determine the presence of liver fibrosis. Results : Among the 88 patients, 38 were classified as having significant fibrosis. In the univariate analysis, muscle mass percentage (MMP), muscle-to-fat ratio (MFR), waist-to-hip ratio (WHR), body mass index, impaired fasting glucose or diabetes mellitus, and alanine transaminase (ALT) level were all significantly associated with fibrosis (P<0.001). After adjusting for ALT level, height, and age, MMP and WHR were associated with fibrosis. Conclusion : In young adults, MMP and MFR were significantly associated with hepatic fibrosis.